2015
DOI: 10.1051/0004-6361/201425554
|View full text |Cite
|
Sign up to set email alerts
|

TheGaia-ESO Survey: A globular cluster escapee in the Galactic halo

Abstract: A small fraction of the halo field is made up of stars that share the light element (Z ≤ 13) anomalies characteristic of second generation globular cluster (GC) stars. The ejected stars shed light on the formation of the Galactic halo by tracing the dynamical history of the clusters, which are believed to have once been more massive. Some of these ejected stars are expected to show strong Al enhancement at the expense of shortage of Mg, but until now no such star has been found. We search for outliers in the M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 50 publications
3
53
0
Order By: Relevance
“…Previous work has indeed suggested the presence of a possible gradient in the incidence of N-rich stars (Carollo et al 2013) in the Galactic halo. Considering also the fact that stars with second generation abundances have been found in the halo (e.g., Martell et al 2011;Carretta et al 2010;Carollo et al 2013;Lind et al 2015;Fernandez-Trincado et al 2016), it seems natural to conclude that an association of our N-rich population to the inner halo seems more likely than to the thick disk. The discrepancy with the numbers expected in other regions of the halo (e.g., Martell et al 2011Martell et al , 2016 indicates that the frequency of N-rich stars may be higher in the inner halo, which is in and of itself an important constraint on models for the origin of this population.…”
Section: Bulge Thick Disk or Halo?mentioning
confidence: 97%
“…Previous work has indeed suggested the presence of a possible gradient in the incidence of N-rich stars (Carollo et al 2013) in the Galactic halo. Considering also the fact that stars with second generation abundances have been found in the halo (e.g., Martell et al 2011;Carretta et al 2010;Carollo et al 2013;Lind et al 2015;Fernandez-Trincado et al 2016), it seems natural to conclude that an association of our N-rich population to the inner halo seems more likely than to the thick disk. The discrepancy with the numbers expected in other regions of the halo (e.g., Martell et al 2011Martell et al , 2016 indicates that the frequency of N-rich stars may be higher in the inner halo, which is in and of itself an important constraint on models for the origin of this population.…”
Section: Bulge Thick Disk or Halo?mentioning
confidence: 97%
“…A small number of studies have done exactly this, searching large collections of spectroscopic data for field stars that follow the globular cluster abundance pattern. Martell & Grebel (2010) and Martell et al (2011) used the Sloan Digital Sky Survey (SDSS)-II/SEGUE (Yanny et al 2009) and SDSS-III/SEGUE-2 (Eisenstein et al 2011) surveys, respectively, as their data sources, while Carretta et al (2010a) and Ramírez et al (2012) used literature compilations originally assembled for other purposes, and Lind et al (2015) used the Gaia-ESO Survey (Gilmore et al 2012). Due to differences in the data available to the various authors, a number of different chemical tags have been used to identify these migrant stars, but all involve some part of the characteristic globular cluster abundance pattern.…”
Section: Chemical Tagging Of Migrant Field Starsmentioning
confidence: 99%
“…Lind et al (2015) argue that stars with low [Mg/Fe] ratios are commonly found in dSph galaxies. However, [Al/Fe] enhancement is not expected in these systems (see Koch & McWilliam 2008).…”
Section: Possible Originsmentioning
confidence: 99%